Glutamine and Alanyl-Glutamine Increase RhoA Expression and Reduce Clostridium difficile Toxin-A-Induced Intestinal Epithelial Cell Damage. (27th December 2012) - Santos, Ana A. Q. A.; Braga-Neto, Manuel B.; Oliveira, Marcelo R.; Freire, Rosemeire S.; Barros, Eduardo B.; Santiago, Thiago M.; Rebelo, Luciana M.; Mermelstein, Claudia; Warren, Cirle A.; Guerrant, Richard L.; Brito, Gerly A. C.
Abstract : Clostridium difficile is a major cause of antibiotic-associated colitis and is associated with significant morbidity and mortality. Glutamine (Gln) is a major fuel for the intestinal cell population. Alanyl-glutamine (Ala-Gln) is a dipeptide that is highly soluble and well tolerated. IEC-6 cells were used in the in vitro experiments. Cell morphology was evaluated by atomic force microscopy (AFM) and scanning electron microscopy (SEM). Cell proliferation was assessed by WST-1 and Ki-67 and apoptosis was assessed by TUNEL. Cytoskeleton was evaluated by immunofluorescence for RhoA and F-actin. RhoA was quantified by immunoblotting. TcdA induced cell shrinkage as observed by AFM, SEM, and fluorescent microscopy. Additionally, collapse of the F-actin cytoskeleton was demonstrated by immunofluorescence. TcdA decreased cell volume and area and increased cell height by 79%, 66.2%, and 58.9%, respectively. Following TcdA treatment, Ala-Gln and Gln supplementation, significantly increased RhoA by 65.5% and 89.7%, respectively at 24 h. Ala-Gln supplementation increased cell proliferation by 137.5% at 24 h and decreased cell apoptosis by 61.4% at 24 h following TcdA treatment. In conclusion, TcdA altered intestinal cell morphology and cytoskeleton organization, decreased cell proliferation, and increased cell apoptosis. Ala-Gln and Gln supplementation reduced intestinal epithelial cell damage and increased RhoA expression.